Respostas

2013-11-02T21:25:32-02:00
A)   \sqrt{2x-1} =x - 2
eleva os dois ao quadrado: 2x -1=  x^{2}  - 4x + 4
6x -  x^{2} - 5=0
Soma=6      x=5
Produto=5   x=1
Verificação(x=5): \sqrt{2 . 5 - 1} =5 - 2
 \sqrt{9} =3
3=3                            x=5(Verdadeiro)

Verificação(x=1): \sqrt{2 . 1- 1} =1-2
 \sqrt{1} = -1
1= -1                   x=1(falso)

B)  5 .  \sqrt{6-m} +10m= 5m
5.  \sqrt{6-m} = - 5m
 \sqrt{6-m}  = m^{2}
   -m^{2}   + 6 - m=0
S=1        M=2
P= - 6     M= - 3 
Verificação(m= - 3):
5 . \sqrt{3 +6} + 30=15
5.3+30=15
45=15              m= - 3 (F)
Verificação(m=2):
5. \sqrt{8} +20=10
100 . \sqrt{8}  =10            m= 2 (F)
 
C)Nao consegui fazer

D)   \sqrt{x} +  \sqrt{x+7=7(eleva ao quadrado)
x + x + 7=49
2x=42
x=21
Verificação: \sqrt{21} + \sqrt28=7
 \sqrt49=7
7=7      x=21(V)
                                        Espero nao ter errrado nada!!